A study on the awareness on advokasi programs among the road users in Kota Kinabalu / Mohd. Haris Marsaling and Mohd Nas Hafiziee Abdullah - Marsaling, Mohd. Haris; Abdullah, Mohd Nas Hafiziee (2012)
The purpose of this study were to examine public awareness towards ADVOKASI in Kota Kinabalu, relationship between JKJR roles and awareness of the public, relationship between JKJR roles and public attitude towards road safety, and relationship between public awareness towards road safety and public attitudes towards road safety. This study was done using self-developed questionnaire involving 250 road users within Kota Kinabalu. We found that the public awareness towards ADVOKASI programs was high, JKJR roles and awareness of the public was very high, JKJR roles and attitudes of the road user, and public awareness towards road safety and public attitudes towards road safety were moderate. From this study, we can conclude that the public awareness level of ADVOKASI programs was high and the public knows the roles played by JKJR which effecting their awareness level and attitudes towards road safety.